Health-care-associated infection in Africa: a systematic review - Sepideh Bagheri Nejad; Benedetta Allegranzi; Shamsuzzoha B Syed; Benjamin Ellis; Didier Pittet (Bulletin of the World Health Organization, 2011)
OBJECTIVE: To assess the epidemiology of endemic health-care-associated infection (HAI) in Africa. METHODS: Three databases (PubMed, the Cochrane Library, and the WHO regional medical database for Africa) were searched to identify studies published from 1995 to 2009 on the epidemiology of HAI in African countries. No language restriction was applied. Available abstract books of leading international infection control conferences were also searched from 2004 to 2009. FINDINGS: The eligibility criteria for inclusion in the review were met by 19 articles, only 2 of which met the criterion of high quality. Four relevant abstracts were retrieved from the international conference literature.The hospital-wide prevalence of HAI varied between 2.5% and 14.8%; in surgical wards, the cumulative incidence ranged from 5.7% to 45.8%.The largest number of studies focused on surgical site infection, whose cumulative incidence ranged from 2.5% to 30.9%. Data on causative pathogens were available from a few studies only and highlighted the importance of Gram-negative rods, particularly in surgical site infection and ventilator-associated pneumonia. CONCLUSION: Limited information is available on the endemic burden of HAI in Africa, but our review reveals that its frequency is much higher than in developed countries.There is an urgent need to identify and implement feasible and sustainable approaches to strengthen HAI prevention, surveillance and control in Africa.